Anders Breivik’s manifesto: measuring violence indicator in anti-Islamic extremist discourse - Cabrera Cusi, Mariet Rosnaida; Abdelaziz, Berghout (IIUM Press, 2024)
On July 22, 2011, Anders Breivik massacred 75 people in a bomb attack and mass shooting out of his hatred towards Islam and Muslims. His actions shocked Norway and the world. He left behind a manifesto ‘2083, A European Declaration of Independence’ which clearly indicates his imagination about Islam and Muslims and the reasons that led him to commit this mass murder. Breivik is studied extensively in the academia through the lenses of Islamophobia and terrorism; there are few studies done on the levels of violence in anti-Islamic discourse. This study uses Richard A. Nielsen’s methodology which measures numerically to which extent Muslim clerics support for violent jihad and ideology in their writings. Such algorithmic approaches that evaluate extremist Muslim discourse have been mainly applied in Western academia to show level of violence in it. This study is unique as the Nielsen’s approach is applied to anti-Islamic extremist discourse. It takes Breivik’s manifesto as a field of analysis. First, it takes as a baseline the five topics (along its exclusive and its frequent keywords) in Jihadi corpus calculated by Professor Nielsen. Second, main key-terms of Breivik’s anti-Islamic position are measured to see the level of violence according to Nielsen’s methodology. After this, both key terms are compared. Results show that Breivik’s anti-Islamic position contains more violence indicator than the jihadist position. This research will be the first to apply algorithmic approach and it will demonstrate that using extremism measure tools developed by the Western academic can be applied to anti-Islamic extremist discourse. In conclusion, if extremism measure tools are applied fairly on both Islamist thought and anti-Islamic discourse, it will not only show that both streams of discourse contain levels of violence, but anti-Muslim discourse accommodates higher levels of violence as well. This research will open the way for Muslim academics to apply algorithmic methods to counter anti-Islamic discourse.